Structural and Thermal Evolution of the Siwaliks of Western Nepal - Mugnier, J. L.; Chalaron, E.; Mascle, G.; Pradier, B.; Herail, G. (Journal of Nepal Geological Society, 1995)
The piedmont of the Himalayas is formed in Western Nepal by: a) Siwalik sediments affected by folds, thrust and back thrust structures and b) intra-belt basins (Duns) that are dis laced piggyback above the thrust sheets. Vitrinite reflectance values (VRo) are found between 0.3% and 0.5% in Middle Siwalik sediments and between 0.6 and 1% in Lower Siwaliks. The thermal maturity of the organic matter agrees with maximum burial depth (3500 m for Middle Siwaliks and 6000 m for Lower Siwaliks) that do not strongly exceed the stratigraphic thickness of the Siwaliks Group. Intense erosion concomitant with deformation balances closely tectonic thickening and prevent burial of the Siwalik sediments at great depth. Nonetheless, Duns developed above the steeper part of the basal decollement and/or ahead of back-thrusts prevent the exhumation of rock and could lead to greater burial depth.